E-Prescription: Connecting Patients’ Prescriptions with Pharmacists and Cashiers - Susilawati, Helfy; Wiharso, Tri Arif (Universitas Muhammadiyah Surakarta, 2021)
The paper describes the development of an electronic prescription system. Electronic prescription or e-prescription is an innovation in the health sector that enables patients to read the types of medication they will receive along with its description and rational use. E-prescription shortens the waiting time to get a prescription, which is different from a manual prescription system. In conventional systems, patients must undergo several steps to get served. They have to give the prescriptions to the cashier and wait for the cashier to calculate the bill. They later submit the proof of payment to the pharmacists and wait for the pharmacist to produce the medicine. Using e-prescription, the patients only have to pay for prescription and wait for the pharmacists to bring the medicine. The waiting time may decrease from 4 complicated steps into 2 simple ones. The website-based e-prescription application enables physicians to electronically send prescriptions to pharmacy computers and send its bill to the cashier. The system allows patients to directly move to the pharmacy once they have paid the bill. The research adopts a quantitative method with a prototype research model and UAT (User Acceptance Test) model for testing.